Rainfall - Runoff Modelling For The Batu Kurau River Basin Using Hec-Hms Model - Hamim, Nur Syafiqah (Universiti Sains Malaysia, 2021)
Changes in land use and urbanization have always been blamed as among the causes of a major increase in magnitude and frequency of flooding. Flash floods occurred in Batu Kurau basin due to drainage capacity is not possible to accommodate the quantity of water as the capacity of the runoff increases. When the quantity of runoff is increased and filling all drains and rivers, floods will occur. Therefore, the purpose of this study is to conduct rainfall-runoff modelling exercises using the HEC-HMS Model, determining the relationship of rainfall-runoff relationship at Batu Kurau basin, Perak, and to get a suitable model to simulate the streamflow hydrograph after calibration and validation process. HEC- HMS is one of the common rainfall-runoff models released by the US Army Corps. The hydrograph generated from the software will determine the rainfall and runoff. It is necessary to understand the relationship between land use and catchment response. Rainfall-runoff models are widely used in predicting changes in hydrologic processes. Analysis of the land use changes on the catchment runoff showed that conversion from forest to agricultural land area increases show the highest increased in peak discharge and runoff volume. Hydrological data such as rainfall and streamflow are important to simulate the rainfall and runoff process in this software. In this study, Nash Sutcliffe Efficiency was used to verify the model calibration and validation. The model efficiency, for calibrated and validated model is 0.954 and 0.922 respectively, which is acceptable correlation between the observed and simulated data.